2006
DOI: 10.1007/bf02913098
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation of fish oils

Abstract: Fish and fish oils are the richest sources of ω-3 fatty acids. However, they are susceptible to lipid peroxidation due to their high degree of unsaturation. In the present study, the level of thiobarbituric acid reactive material in various fish oils available in the market with and without added Vitamin E was determined. The peroxide levels in fish oil heated to food frying temperature of 180 0 C and the effect of addition of vitamin E has also been studied. The results indicate that the peroxide levels in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
(3 reference statements)
1
8
0
Order By: Relevance
“…The antiperoxidant effect of the ethanolic extract which was observed to be concentration dependent was similar to the findings of a previous study elsewhere (Prasad and Ramakrishnan, 2012) where the lipid peroxide radical scavenging potential of Rumex vesicarius was investigated. The inhibitory lipid peroxidation potential of the extract and fractions reflects their ability to probably reduce the risk factors associated with the induction and development of atherosclerosis (Godwin and Prabhu, 2006); slow down the aging process and boost immune responses (Prasad and Ramakrishnan, 2012). The lipid peroxidation inhibitory capacity of the extract and fractions is also very remarkable as it can be linked to the ability of the plant to prevent peroxidative damage to the plasma membrane of the sperm and loss of DNA structural integrity.…”
Section: Antioxidant Studymentioning
confidence: 99%
“…The antiperoxidant effect of the ethanolic extract which was observed to be concentration dependent was similar to the findings of a previous study elsewhere (Prasad and Ramakrishnan, 2012) where the lipid peroxide radical scavenging potential of Rumex vesicarius was investigated. The inhibitory lipid peroxidation potential of the extract and fractions reflects their ability to probably reduce the risk factors associated with the induction and development of atherosclerosis (Godwin and Prabhu, 2006); slow down the aging process and boost immune responses (Prasad and Ramakrishnan, 2012). The lipid peroxidation inhibitory capacity of the extract and fractions is also very remarkable as it can be linked to the ability of the plant to prevent peroxidative damage to the plasma membrane of the sperm and loss of DNA structural integrity.…”
Section: Antioxidant Studymentioning
confidence: 99%
“…For example, the addition of α-tocopherol to commercially available fish oils exposed to the food frying temperature of 180°C had a profound effect on lowering the rate of peroxidation, indicating a strong protective effect for antioxidants at lowering the rate of thermally induced lipid peroxidation in PUFAs. 62 D'Souza et al, 62 added turmeric (containing the antioxidant curcumin) to the flesh of both raw and cooked mackerel before cooking at 100°C and reported a significant reduction in lipid peroxides in the extracted mackerel oil. A further study by Sekhon-Loodu et al 63 added 200 µg/ml polyphenols isolated from frozen and dried apple peels and observed a significant reduction in lipid peroxidide formation rate of up to 62 %.…”
Section: Figurementioning
confidence: 99%
“…Industrialization and overgrowing urbanization are also suspected as causes of human exposure to different toxic chemicals. They may compromise the male reproductive system and produce cellular impairment both at structural and functional level (Beckman et al, 1990 ; Godwin et al, 2006 ). Xenobiotics alter the structure of the cell membrane by stimulating the lipid peroxidation process with ensuing complex sequences of biochemical reactions.…”
Section: Introductionmentioning
confidence: 99%